Functional rehabilitation in neurosurgery and neurotraumatology - Wild, Klaus R. H. von; Lipovšek, M; Mendelow, A. D; Truelle, J. L (Springer, 2002)
Clemens Hospital, Munich, Germany. Selected papers from two meetings present a comprehensive overview of concepts, strategies, state-of-the-art treatment, and results of early and longlasting neurorehabilitation and reintegration into the social environment. First volume in a new series on \'rehabilitation in neurosurgery.\'
Acta neurochirurgica, ISSN 0065-1419 suppl. 79, 2002
Keywords: Rehabilitation; neurochirurgie; poranění mozku; Brain Injuries; Neurosurgery; neurochirurgické výkony; Neurosurgical Procedures; traumatologie; rehabilitační a fyzikální medicína; rehabilitace; Traumatology